TANGGUNG JAWAB NOTARIS ATAS AKTA DIBAWAH TANGAN YANG DILEGALISASI SEBAGAI ALAT BUKTI DI PENGADILAN - Mario Sembiring Meliala; Felicitas Sri Marniati; Putra Hutomo (Bajang Institute, 2026)
In proving a privately drawn deed in Court, one of the judge's duties is to investigate the truth of a legal relationship that is the basis of a lawsuit. A privately drawn deed legalized by a notary, as long as it is not denied or disputed by the parties, has the same legal force as an authentic deed. The problems in this study are how is the position of a privately drawn deed legalized by a Notary as court evidence, and the Notary's liability for a privately drawn deed legalized as court evidence. The theories used are the theory of proof according to H. Riduan Syahrani and the theory of legal liability according to Hans Kelsen. The method used in this research is a normative juridical research type, namely library research or secondary data with primary, secondary, and tertiary legal material sources. With the Legislation approach, Case Approach Analytical Approach, Conceptual Approach and Legal material collection techniques are carried out by identifying and inventorying positive legal regulations, book literature, journals and other legal material sources. For analysis techniques with grammatical interpretation, systematic interpretation, Analogy Construction and Legal Refinement Construction. This study examines the legal implications of claims based on privately executed deeds that have been legalized by a notary. As long as the privately executed deed is not denied or disputed by the parties, it possesses evidentiary value equivalent to that of an authentic deed. However, if the authenticity of the signatures contained in the privately executed deed is contested, the validity of the deed must be proven through other means of evidence, such as witness testimony, presumptions, and admissions. Furthermore, this research analyzes the notary’s responsibility in relation to the legalization of privately executed deeds. The notary’s responsibility is limited to providing certainty regarding the authenticity of the signatures and the date of execution. Legalization by a notary ensures that the signatures affixed to the deed genuinely belong to the parties to the agreement and not to any other person, as well as providing certainty as to the date on which the deed was signed.